ME AND MYSELF: SELF-CONCEPT OF THE YOUNG ADOLESCENT LEARNERS - Bhatti, Dr. Muhammad Tariq; Teevno, Dr. Roshan Ali (The journal of contemporary issues in business and government, 2021)
The study assessed the self-concept of rural and urban adolescents. The stratified random sampling technique was used to select rural and urban adolescent students from Karachi, Sindh province in Pakistan. The total number of adolescent students selected for the study was 12000 which consist of 6000 rural (3000 boys and 3000 girls) and 6000 urban students (3000 boys and 3000 girls). The Belbin’s Self Perception Inventory (SPI) was used for data collection and some statistical methods like descriptive and inferential methods were used for data analysis. The results confirmed that urban adolescent students showed greater self-evaluation and aspiration than rural adolescent students. The category-wise data showed that urban adolescent students led rural adolescents in both genders on self-evaluation and aspiration.